The effects of microalloying on the precipitate microstructure at grain boundary regions in an Mg-Zn-based alloy. (5th April 2017) - Langelier, B.; Sha, G.; Korinek, A.; Donnadieu, P.; Ringer, S.P.; Esmaeili, S.
Abstract: Microalloying additions to Mg-Zn base alloys can refine precipitation and improve hardening, but their effect on the microstructure at the grain boundary regions are seldom analyzed. Here the grain boundary microstructure is examined in an Mg-4Zn (wt.%) alloy, which has been microalloyed with Ce-Ca. This combination of elements has previously been shown to successfully enhance ductility, texture, and precipitation hardening, compared to binary Mg-Zn. Coarse grain boundary precipitates are found with or without microalloying, but precipitate-free zones (PFZs) for β ′1 that surround the boundaries are far narrower with Ce-Ca microalloying additions. Furthermore, fine basal precipitates containing Ca are found uniformly distributed up to the boundary, making those zones devoid of β ′1 not truly precipitate-free. Electron microscopy and atom probe analysis of early-stage ageing conditions reveals that Ca readily forms clusters with Zn, and forms fine ordered GP zones, while Zn also segregates to the grain boundaries. The tendency of Ca to homogeneously form clusters and precipitates reduces Ca migration to the grain boundaries, which has a beneficial effect on producing the refined precipitate distributions at the grain boundary regions. Graphical abstract: Highlights: Precipitation behaviour at grain boundary regions in an Mg-Zn alloy is improved by microalloying with Ce-Ca. Refined precipitation and reduced precipitate-free zones are achieved, primarily by action of the microalloying element Ca. Ca begins modifying precipitation behaviour during early-stage ageing; when Zn primarily segregates to the boundaries, Ca instead forms uniformly-dispersed clusters. The clustering tendency of Ca promotes GP zone formation and evenly-distributed fine precipitates, even at grain boundary regions. These findings highlight microalloying as a viable alloy design strategy for improving precipitation characteristics at grain boundary regions.